ANALISIS PENGGUNAAN INFORMASI AKUNTANSI SEBAGAI DASAR PENGAMBILAN KEPUTUSAN DAN EVALUASI KINERJA DI TINGKAT SATUAN KERJA PADA KANTOR KEMENTERIAN AGAMA KABUPATEN MINAHASA TENGGARA - Lamia, Steldy; Karamoy, Herman; Morasa, Jenny (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This research aims to analyze how the use of accounting information by state treasury officials in decision making and performance evaluation, to analyze constraints in the use of accounting information for state treasury officials and analyze efforts that must be made to overcome obstacles in the use of accounting information as a basis for decision making and performance evaluation This research uses qualitative methods with a case study approach. This research uses qualitative methods with a case study approach. Data collection is done by means of in-depth interviews, observations, and documentation studies. The data analysis used in this study was the analysis of miles and Huberman models, and for data validity testing using triangulation techniques. The results of the study showed that the use of accounting information as a basis for decision making and performance evaluation to run office operations in the public sector such as in the Office of the Ministry of Religious Affairs of Southeast Minahasa Regency is very important because through the accounting information in the report, our finances can determine more appropriate policies in evaluating the program of activities or for the preparation of budget plans in the coming year. The causes of the less than optimal use of accounting information by State Treasury Officials at the Office of the Ministry of Religion of Southeast Minahasa Regency are human resources with incompetent educational backgrounds, the habit of overriding accounting information as a basis for entrenched decision making and the lack of support for supporting facilities that can help efficiency and effectiveness with respect to the use of this accounting information. Efforts that can be made to overcome these problems include increasing the competence of knowledge and expertise of existing human resources, building commitment and providing supporting facilities.